Link Adaptation and Carriers Detection Errors in Multibeam Satellite Systems with Linear Precoding - Anxo Tato; Stefano Andrenacci; Chatzinotas, S.; Carlos Mosquera (9th Advanced Satellite Multimedia Systems Conference (ASMS) and 15th Signal Processing for Space Communications Workshop (SPSC), 2018)
The application of linear precoding at the gateway side enables broadband multibeam satellite systems to use more aggressive frequency reuse patterns increasing the overall capacity of future High Throughput Satellites (HTS). However, although some previous works about precoding consider imperfect CSIT (Chanel State Information at the Transmitter) adding some CSI estimation errors, that is not the main cause of CSI degradation. In practice, receivers can only detect and estimate a few coefficients of the CSI vector being the other nullified, replaced by zeros. This introduces errors in the SINR calculation by the gateway that lead to the assignment of Modulation and Coding Schemes (MCS) over the decoding possibilities of the users, increasing the rate of erroneous frames. In this work, the errors in the SINR calculation caused by the nullification of the CSI are analyzing statistically and geographically using a radiation diagram of 245 beams over Europe. Furthermore, a solution based on a link adaptation algorithm with a per user adaptive margin is proposed, helping to achieve the QEF (Quasi-error Free) target of DVB-S2X systems.